Bridging therapeutic landscapes to architecture. International experience-based design strategies for healthcare infrastructures - Cardoso Arevalo, Karla Johanna; Rebecchi, Andrea; Botta, Monica; Gola, Marco; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: in Italy, many cases studies of therapeutic green spaces are built into healthcare infrastructures, but only some of these follow the principles of healing gardens. Scientific literature and international case studies offer many contributions of evidence relating to how therapeutic green spaces can support traditional treatments. The paper analyze the relationship between indoor and outdoor spaces and healing gardens’ features; the main research questions were: “Can we synthetize experience-based design strategies for therapeutic green spaces and healing gardens? How can we prioritize the most relevant ones for the healthcare infrastructures?” Methods: Research Method is divided into three different steps: 1st case studies’ selection; 2nd case studies’ analysis, and 3rd quali-quantitative comparative matrix. Results: ten case studies were identifiedfour of them have the therapeutic green space on the ground floor,despite of the other six having the healing garden on the rooftop.The best experience-based design strategies for the therapeutic green spaces or healing gardens development were identified from the previous comparison matrix, and divided into A.Safety, Security and Privacy; B.Accessibility; C.Physical and Emotional Comfort; D.Positive distraction; E.Engagement with Nature; F.Maintenance and Aesthetics; and G.Sustainability. Conclusions: The results obtained from the comparative matrix are qualitative and quantitative design elements in terms of type of element / space, percentage, perimeter, area, number, materiality, shape, color, among others. The quali-quantitative matrix is a useful and practical tool that allows the designer to have a base of design guidelines that can be later applied to the proposal of new therapeutic gardens.